Joyful learning inside and beyond the classroom: integrating guided field trips to festivals and events in higher education - Estrella Sendra (Journal of Learning Development in Higher Education)
This article advocates for joyful learning through active participation in events beyond the classroom and critical reflection within the classroom. It responds to the call from educators for studies on designing learning methods that promote well-being by examining an experiential learning method that fosters joy: integrating guided field trips to festivals and events in higher education. Learning in the context of a world facing multiple crises can be challenging. Despite efforts by Higher Education Institutions to create inclusive and liberating environments, rigid grading systems often foster competition among students. This article focuses on the benefits of guided study field trips across undergraduate and postgraduate Arts and Humanities programmes at Winchester School of Art (University of Southampton), SOAS, University of London, and King’s College London. Guided study field trips, curated by tutors, align with module learning outcomes. Inspired by bell hooks’ emphasis on excitement in education, Paulo Freire’s problem-solving approach, and Lynne Segal’s radical understanding of joy, I suggest that these trips embrace the curatorial turn in education, allowing students to acquire subject-specific and social skills. They foster a joyful, collegial, caring, and respectful environment, disrupting hierarchical classroom relations and fostering connection, well-being, and collaboration in teamwork. This experience encourages students to engage in a continuous dialogue from the classroom to the world beyond, facilitates informed decision-making processes, and boosts confidence in students' agency to transform the world.